Characterization of the vip3A gene and toxicity of Vip3Aa50 protein to fall armyworm and velvetbean caterpillar - Figueiredo, Camila Soares (2013)
The objective of this work was to characterize the vip3A gene of Bacillus thuringiensis and to evaluate the toxicity of Vip3Aa50 protein to the fall armyworm (Spodoptera frugiperda) and velvetbean caterpillar (Anticarsia gemmatalis) larvae. The gene vip3A was amplified by specific PCR primers, generating a 2,370‑bp fragment. This fragment was cloned into the pGEM‑T Easy vector, and then it was sequenced, subcloned into the pET‑28a (+)’s expression vector, and inserted into Escherichia coli BL21 (DE3) cells. The Vip3Aa50 protein expression was induced by isopropyl‑β‑D‑1‑thiogalactopyranoside (IPTG), visualized in SDS‑PAGE, and detected by Western blot. The toxicity bioassay showed a high activity of Vip3Aa50 protein against both velvetbean and fall armyworm neonate larvae, with LC50 at 20.3 and 79.6 ng cm-2 respectively. The vip3Aa50 gene, is a new gene of vip3A class.